Dynamics of a Prey-Predator System with Harvesting Effect on Prey - Özlem Ak Gümüş (Chaos Theory and Applications, 2022)
This article is about the dynamic behavior of a prey-predator model exposed to the harvesting effect on prey. Firstly, the existence and stability of the fixed points of the model are obtained, and then the presence and direction of Neimark-Sacker bifurcation is examined. By using the bifurcation theory, we show that the system undergoes Neimark-Sacker bifurcation. The hybrid control strategy is applied to control the chaos caused by the Neimark-Sacker bifurcation. In addition, some numerical simulations are given to verify the theoretical results obtained.